Teaching Distributed Work Practices:: the Liquid Campus - RUSSELL, Peter; ELGER, Dietrich (ARCC Conference Repository, 2019)
The paper describes an educational project using methods similar to those described as virtual design studios. This term, however, is avoided by the authors as it is used by other educators in projects ranging from relatively simple CAAD courses to those who share files over the internet between separated groups of students. The design studio spanned six universities over an entire semester using both physical and virtual environments. It is named: The Liquid Campus. The focus of the Liquid Campus was to teach distributed work practices to a collection of upper level architecture students using Internet based communication methods. Indeed, the authors contend that these work practices are better trained than taught. In the summer of 2001, forty-three students from six different universities took part in the 3 1/2- month project. The students worked as teams of three (with one group of four) with each member of the team coming from a different university. Furthermore, each student team was assigned a tutor coming from a fourth university. By setting these strict ground rules, the authors were able to truly test the ability of the students to work over the Internet with one another to achieve a design solution. The physical separation of all partners was essential in precluding other communication methods such a face to face meeting. The semester began with a three-day workshop in which all students and tutors took part. This served to introduce the design problem, but more importantly, to allow social interaction between the potential partners. Short research assignments and social time allowed the students and tutors to get to know one another before the groups were set on the last day of the workshop. The entire group met again 15 weeks later for a final review, although individual teams met with their respective tutors halfway through the project. The participants used a co-operation platform developed at one of the partner institutes as a common information and co-ordination centre. Indeed, the platform became the "place" to meet to discuss ideas generated from the design problem. The platform served as a directory of web-based student work, schedules, tutorial sessions as well as a repository of contact and research information for the participants. The individual teams established their own rhythms for meeting and working on their design solution. The design theme itself was somewhat self-referential in nature. The students were to design a place for members of a virtual university (such as the WINDS project currently being funded by the European Commission in the 5th Framework program). Thus, the students worked in, on and within the same set of design parameters. While this overlay of design method and design problem was taxing for the students, it also lead to a wide band of design solutions ranging from completely virtual to mostly physical "places". All 14 teams successfully completed the project. Questionnaires following the final review show an overwhelmingly positive resonance from the students. The paper discusses the results of the project as well as an assessment of the value of the project in relation to its relatively high organisational costs.